Bariatric surgery trends and progress in Taiwan: 2010–2021. Issue 1 (January 2023) - Hsu, Kuo-Feng; Pan, Hsin-Mei; Chang, Po-Chih; Huang, Chih-Kun; Wang, Weu; Lee, Wei-Jei; Soong, Tien-Chou; Lee, Ming-Hsien; Yang, Po-Jen; Hsin, Ming-Che; Lin, Chien-Hua; Liao, Guo-Shiou
Abstract: Introduction: Taiwan is a leading country regarding bariatric surgery in Asia-Pacific. Since 2010, the Taiwan Society for Metabolic and Bariatric Surgery (TSMBS) has been accountable for the national evolution of bariatric surgery and inaugurated a national database accordingly. This study aimed to analyze the bariatric surgery trends and progress in Taiwan from 2010 to 2021. Materials and methods: The TSMBS database was collected on the basis of structured inquiries filled out by bariatric surgeons in Taiwan. All patients involving bariatric surgery were included. The data were stratified with the following objectives, including the types of bariatric procedures, demographic characteristics, and perioperative variables. A nationwide database was comprehensively analyzed and evaluated to determine the trends in the applications of the procedure. Results: Data of 30, 026 patients were enrolled. A 2.5-fold increase was observed in bariatric procedures, from 1218 in 2010 to 3005 in 2021. Within 12 years, female accounts for 61.8 %. The revisional rate was 3.40 % during the exploration stage (2010–2013), 2.77 % during the maturity stage (2013–2018), and 5.10 % during the expansion stage (2019–2021). The top five of primary bariatric surgery is sleeve gastrectomy (SG, 63.05 %), gastric clipping surgery (GC, 11.17 %), Roux-en-Y gastric bypass (RYGB, 9.34 %), one anastomosis gastric bypass (OAGB, 8.80 %), and sleeve plus surgery (SG plus, 4.43 %). Conclusion: The trends and progress of Taiwan's bariatric surgery within recent decades are presented in this article. Taiwan's bariatric surgery case number has increased steadily from 2010 to 2021. Amongst all, SG has become the most dominant procedure since 2011 while OAGB takes up second place in 2020. Highlights: Taiwanis the pioneer of bariatric surgery in the Asia Pacific since the late 20th century. To comprehensively demonstrate a panorama of Taiwan's bariatric surgery development. Several factors influencing the ebb and flow of various bariatric surgery procedures in Taiwan are discussed. The trends of Taiwan's bariatric surgery may provide an insight of the evolvement of bariatric surgery in Asian population.